Application of the Viable System Model to analyse communications structures: A case study of disaster response in Japan - Preece, Gary; Shaw, Duncan; Hayashi, Haruo (European journal of operational research, 2015)
Every year, natural and man-made disasters affect hundreds of thousands of people and cause extensive damage. OR has made substantial contributions to disaster response and these have been the subject of several recent literature reviews. However, these reviews have also identified research gaps for OR – two of which are (1) limited contribution from soft OR, and (2) a need to model communications during disasters where there are complex interactions between stakeholders. At the intersection of these gaps we apply the Viable System Model (VSM) to examine challenges of rapid communication viability during dynamic disasters. The data that informs this paper were collected in four case studies in Japan – three on its current capabilities (e.g. a local government disaster management office) and one on its response to a past disaster (the Great Hanshin-Awaji Earthquake in 1995). This paper shows how applying VSM identified generic gaps and opportunities for communication systems and shows how these case studies signal the utility of VSM structures to arranging communications for fast-paced and changing environments. This paper also contributes to VSM theory through developing two new concepts (1) environmental support mechanisms for viability; and (2) rapid implementation unit emergence. •Recent reviews in EJOR (and JORS) have studied OR's contribution to disaster response.•Each review finds little contribution from soft OR or modelling disaster information.•Effective communication is vital to manage disaster response resources.•The Viable System Model (VSM) can examine rapid disaster communication viability.•Four disaster case studies use VSM to identify structural communication faults.